Biodiversity of marine helminth parasites in New Zealand: what don't we know?. Issue 2 (3rd April 2022) - Bennett, Jerusha; Presswell, Bronwen; Poulin, Robert
ABSTRACT: A full account of the world's species is important for understanding how natural systems are structured, how they function and how they will respond to natural and anthropogenic pressures in the future. Despite the well-known importance of parasites in natural systems, they are too often underrepresented from studies on biodiversity and ecological functioning. In this review, we provide a quantitative synthesis of the current state of knowledge of helminth biodiversity within New Zealand's marine environment. We report that records of parasitic helminths within New Zealand marine animals are few and uneven across host taxa. A large proportion of parasite species are taxonomically unresolved, with some differences across parasite taxa. Few parasites have their whole life cycles resolved, and the majority are only reported from one host species at one life stage. Most endemic host species are yet to be investigated for helminths and there is likely an abundance of endemic parasite diversity yet to be discovered. Host species of greater conservation concern are being investigated for helminths less frequently than species of low conservation concern. We conclude that little is known about parasitic helminths in New Zealand's marine environment and make recommendations on how to improve this situation.